Visual recognition and coevolutionary history drive responses of amphibians to an invasive predator. (26th September 2021) - Melotto, Andrea; Ficetola, Gentile Francesco; Alari, Elisa; Romagnoli, Samuele; Manenti, Raoul
Abstract: During biotic invasions, native prey are abruptly exposed to novel predators and are faced with unprecedented predatory pressures. Under these circumstances, the lack of common evolutionary history may hamper predator recognition by native prey, undermining the expression of effective antipredator responses. Nonetheless, mechanisms allowing prey to overcome evolutionary naïveté exist. For instance, in naïve prey, history of coevolution with similar native predators or detection of general traits characterizing predators can favor the recognition of stimuli released by invasive predators. However, few studies have assessed how these mechanisms shape prey response at the community level. Here, we evaluated behavioral responses in naïve larvae of 13 amphibian species to chemical and visual cues associated with an invasive predator, the American red swamp crayfish ( Procambarus clarkii ). Moreover, we investigated how variation among species responses was related to their coexistence with similar native crayfish predators. Amphibian larvae altered their behavior in presence of visual stimuli of the alien crayfish, while chemical cues elicited feeble and contrasting behavioral shifts. Activity reduction was the most common and stronger response, whereas some species exhibited more heterogeneous strategies also involving distancing and rapid escape response. Interestingly, species sharing coevolutionary history with the native crayfish were able to finely tune their response to the invasive one, performing bursts to escape. These results suggest native prey can respond to invasive predators through recognition of generic risk cues (e.g., approaching large shapes), still the capability of modulating antipredator strategies may also depend on their coevolutionary history with similar native predators. Abstract : We assessed behavioral response in larvae of 13 amphibian species to chemical and visual cues of an invasive crayfish predator. Most of the species recognized visual but not chemical cues of the novel predator, showing heterogeneous anti-predator strategies. Species sharing an evolutionary history of coexistence with similar native crayfish finely tuned their response to the invasive. These findings highlight mechanisms favoring the recognition of novel predators and the activation of anti-predator responses in native prey.